Management of primary biliary cholangitis: results from a large real-life observational study in France and Belgium. Issue Volume 33:Issue S1(2021) (30th November 2020) - Pariente, Alexandre; Chazouilleres, Olivier; Causse, Xavier; Hanslik, Bertrand; Arpurt, Jean-Pierre; Henrion, Jean; Rosa, Isabelle; Renou, Christophe; Garioud, Armand; Corpechot, Christophe; ,
Abstract : Background and aims: To assess the characteristics, care, treatment response, and outcomes of primary biliary cholangitis (PBC) patients recently followed-up by hepato-gastroenterologists in various French and Belgian healthcare settings. Methods: This retrospective cohort study included patients with PBC who recently visited 79 hepato-gastroenterologists in France and Belgium. Data were collected at the time of diagnosis and at last visit and were compared according to biochemical response (BR) to ursodeoxycholic acid (UDCA) (BR), using Paris I–II criteria, and clinical outcomes. Results: A total of 436 patients (mean age at diagnosis 57 years, 88% females, median follow-up 5.2 years) were included. Liver biopsy, transient elastography, or none of these two procedures were performed at baseline in 216 (50%), 194 (45%), and 107 (25%) patients, respectively. Late-stage disease (histological stage III or IV, or transient elastography ≥9.6 kPa, or bilirubin >17 µM and albumin <35 g/L, or platelets <150.000/µl, or unequivocal signs of portal hypertension or cirrhosis) was reported in 37% of patients. UDCA was taken by 95% of patients (27% had suboptimal dosage). Inadequate BR was observed in 37% of patients. Clinicians overestimated disease control. Liver-related complications occurred in 9% of patients. Bilirubin and albumin independently predicted inadequate BR; advanced disease stage and inadequate BR independently predicted complications. Conclusions: Recently followed-up French and Belgian patients with PBC had homogeneous management. Late stage at diagnosis and inadequate BR were reported in around 40% of patients. Disease control was frequently overestimated by clinicians. Disease stage and BR were the main prognostic factors.